High-stability gel foam for inhibiting spontaneous combustion of coal and preparation method of high-stability gel foam

By using Al3+'s high-stable high-valent metal ion gel foam, the problems of poor stability and small coverage in coal spontaneous combustion inhibition are solved, and higher stability and more effective coal spontaneous combustion inhibition are achieved.

CN119746333APending Publication Date: 2025-04-04ZHENGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411823107.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has problems such as poor stability, small coverage, high cost and a great impact on the environment in suppressing coal spontaneous combustion.

Method used

Using Al3+ high-stable high-valent metal ion gel foam, a gel foam with stronger stability and higher apparent activation energy is formed through specific component ratios and preparation methods to effectively inhibit the spontaneous combustion of coal.

Benefits of technology

It achieves higher stability and more effective coal spontaneous combustion inhibition, improves the shortcomings of traditional fire-fighting foams, and has better application effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746333A_ABST
    Figure CN119746333A_ABST
Patent Text Reader

Abstract

The invention discloses high-stability gel foam for inhibiting spontaneous combustion of coal and a preparation method of the high-stability gel foam. The high-stability gel foam comprises the following components in percentage by mass: 0.3% of a foaming agent, 0.5% of a gelatinizing agent, 1.85% of a cross-linking agent, 1.5% of a PH modifier and the balance of deionized water. The gel foam material has the advantages of being stable in structure, good in heat insulation performance, good in water retention performance, good in inhibition performance and the like, oxidation spontaneous combustion of coal can be effectively inhibited, the gel foam material can adapt to the complex coal mine environment, a new thought is provided for the technical field of coal mine fire prevention and extinguishing, and the gel foam material has important practical significance on coal mine safety production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gel foam, and in particular relates to a high-stability gel foam for inhibiting spontaneous combustion of coal and a preparation method thereof. Background Art

[0002] As China's most important fossil energy source, coal supports the country's industrial and energy base. In recent years, China's coal mining volume has always ranked first in the world. Spontaneous combustion of coal is one of the most serious disasters in coal mining. It not only causes a large number of casualties among miners, but also leads to the waste of a large amount of coal resources that cannot be mined and brought huge economic losses. In addition, the large amount of toxic and harmful gases and ground collapse produced by spontaneous combustion of coal will have a huge impact on the surrounding ecological environment.

[0003] At present, the commonly used methods to suppress coal spontaneous combustion include grouting, inert gas injection, inhibitors, gel, foam and other technologies. Although grouting fire extinguishing measures have the advantage of low cost, the slurry has strong fluidity and cannot be accumulated at high places under the action of gravity, so it can only control low-point ignition sources; when injecting gases such as N2 and CO2, the inert gas will escape due to the poor sealing of the mine, and the oxidation of coal cannot be suppressed for a long time; the inhibitor technology is expensive and will endanger the health of underground personnel; the gel technology has a small diffusion range and cannot cover a large area of ​​the coal body. Compared with the above methods, foam is widely regarded as the best way to control coal spontaneous combustion due to its advantages such as large flow rate and wide coverage. However, traditional water-based foams have a short water retention time and poor stability, and cannot cover the coal body for a long time. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a highly stable gel foam for inhibiting spontaneous combustion of coal and a preparation method thereof. The gel foam of the present invention is made of Al 3+ The highly stable high-valent metal ion gel foam not only has stronger stability, but also increases the apparent activation energy of coal, and can more effectively inhibit the spontaneous combustion of coal.

[0005] The high-stable gel foam for inhibiting coal spontaneous combustion of the present invention comprises the following components in terms of mass concentration ratio: 0.3% of foaming agent, 0.5% of gelling agent, 1.85% of cross-linking agent, 1.5% of pH modifier and the balance of deionized water.

[0006] The foaming agent is a mixture of sodium α-olefin sulfonate and lauramide propyl betaine, and the mass concentration ratio of sodium α-olefin sulfonate to lauramide propyl betaine is 2:1.

[0007] The gelling agent is sodium alginate.

[0008] The cross-linking agent is a mixture of disodium ethylenediaminetetraacetate and polyaluminium chloride, and the mass concentration ratio of disodium ethylenediaminetetraacetate to polyaluminium chloride is 17:20.

[0009] The pH modifier is glucono-delta-lactone.

[0010] The invention discloses a method for preparing a high-stable gel foam for inhibiting spontaneous combustion of coal. The high-stable gel foam comprises the following components in terms of mass concentration ratio: 0.3% of a foaming agent, 0.5% of a gelling agent, 1.85% of a cross-linking agent, 1.5% of a pH modifier, and the balance of deionized water. Firstly, the foaming agent and the deionized water are mixed in proportion, stirred evenly to obtain a mixed solution, and then the gelling agent, the cross-linking agent, and the pH modifier are sequentially added to the mixed solution. After the mixture is completely mixed, a mechanical foaming method is used for foaming to form the gel foam.

[0011] The beneficial effects of the present invention are:

[0012] The gel foam of the present invention is a kind of 3+ Highly stable high-valent metal ion alginate gel foam, Al 3+ The gel foam not only has stronger stability, but also improves the apparent activation energy of coal, and can more effectively inhibit the spontaneous combustion of coal. The temperature resistance experiment shows that the structure of this gel foam material is more solid, the foam breaks more slowly at higher temperatures, and it has better thermal insulation; the water retention experiment shows that this gel foam material has better water retention performance; the programmed temperature rise of coal shows that this gel foam material can more effectively prevent the coal sample from contacting with oxygen, thereby inhibiting the generation of CO; the thermogravimetric experiment shows that this gel foam material can more effectively inhibit the weight increase caused by oxygen absorption before the intense combustion of coal, and can increase the temperature point of the maximum water loss rate and the maximum weight loss rate of coal. Therefore, the gel foam prepared by the present invention has good stability and the effect of inhibiting the spontaneous combustion of coal, which can improve the shortcomings of traditional coal mine fire prevention and extinguishing foam and obtain better application effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The foaming volume and liquid separation half-life of sodium α-olefin sulfonate (AOS) and laurylpropyl betaine (LAB) as foaming agents at concentrations of 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35% and 0.4%; a is LAB and b is AOS.

[0014] Figure 2 The foaming performance experiment of compound foaming was carried out using sodium α-olefin sulfonate (AOS) and laurylpropyl betaine (LAB) as foaming agents; a is the foaming volume and liquid separation half-life, and b is the comprehensive foam value.

[0015] Figure 3 Ca 2+ Preparation process of gel foam.

[0016] Figure 4 For water-based foam, Ca 2+ Gel foam, Al 3+ Foam morphology of gel foam at different times when heated in a water bath at 100℃; (a) water-based foam, (b) Ca 2+ -GF, (c)Al 3+ -GF.

[0017] Figure 5 These are the defoaming curves and temperature resistance curves of the three foams.

[0018] Figure 6 Water loss rates of three foams at different temperatures.

[0019] Figure 7 This is a programmed temperature experiment of the original coal sample and the coal sample treated with different gel foams.

[0020] Figure 8 TG and DTG curves of the original coal sample and the coal samples treated with different gel foams; (a) original coal sample, (b) Ca 2+ -GF, (c)Al 3+ -GF. DETAILED DESCRIPTION

[0021] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0022] The high-stable gel foam for inhibiting coal spontaneous combustion of the present invention comprises the following components in terms of mass concentration ratio: 0.3% of foaming agent, 0.5% of gelling agent, 1.85% of cross-linking agent, 1.5% of pH modifier and the balance of deionized water.

[0023] The foaming agent is a mixture of sodium α-olefin sulfonate and lauramide propyl betaine, and the mass concentration ratio of sodium α-olefin sulfonate and lauramide propyl betaine is 2:1. Sodium α-olefin sulfonate is an anionic surfactant with the characteristics of good foaming, low toxicity and good biodegradability, while the amphoteric surfactant lauramide propyl betaine has low irritation and good compatibility, and can be used together with anionic surfactants to play a synergistic role.

[0024] The gelling agent is sodium alginate. Sodium alginate is a natural polysaccharide, mainly extracted from seaweed. Thanks to the fact that sodium alginate can chelate with metal ions and has certain antioxidant properties, sodium alginate is an ideal material for preparing gel foam.

[0025] The cross-linking agent is a mixture of disodium ethylenediaminetetraacetate and polyaluminium chloride, and the mass concentration ratio of disodium ethylenediaminetetraacetate and polyaluminium chloride is 17:20.

[0026] The pH modifier is glucono-δ-lactone.

[0027] First, disodium ethylenediaminetetraacetate and Al in polyaluminium chloride are used 3+ The cross-linking agent was prepared by forming a stable chelate, and the pH value of the solution was adjusted to about 7. When only sodium alginate and disodium ethylenediaminetetraacetic acid were present in the solution, Al 3+ When the chelate is formed, no cross-linking reaction can occur. Then glucono-δ-lactone is added to stimulate the chelate to release Al 3+ , inducing sodium alginate to undergo a gel reaction.

[0028] The invention discloses a method for preparing a high-stable gel foam for inhibiting spontaneous combustion of coal. The high-stable gel foam comprises the following components in terms of mass concentration ratio: 0.3% of a foaming agent, 0.5% of a gelling agent, 1.85% of a cross-linking agent, 1.5% of a pH modifier, and the balance of deionized water. Firstly, the foaming agent and the deionized water are mixed in proportion, stirred evenly to obtain a mixed solution, and then the gelling agent, the cross-linking agent, and the pH modifier are sequentially added to the mixed solution. After the mixture is completely mixed, a mechanical foaming method is used for foaming to form the gel foam.

[0029] Example 1

[0030] The concentration of the foaming agent and the optimal mass concentration ratio of the two substances are determined.

[0031] Sodium α-olefin sulfonate (AOS) and laurylpropyl betaine (LAB) were used as foaming agents for foaming, and experiments were conducted to determine the concentration of the foaming agent.

[0032] like Figure 1 , are the foaming volumes and liquid separation half-lives of two single foaming agents at concentrations of 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, and 0.4%. Figure 1 It can be seen that in the initial stage, as the mass fraction of the two surfactants increases, the foaming volume and the liquid separation half-life continue to increase. When the mass fraction of the two surfactants reaches 0.3%, the increase trend of the foaming volume and the liquid separation half-life tends to be flat, and even declines. Therefore, based on the single foaming experiment, this study selected a total foaming agent concentration of 0.3wt% for the foaming agent compounding experiment.

[0033] Next, sodium α-olefin sulfonate (AOS) and lauryl propyl betaine (LAB) were compounded for foaming. The experimental results are as follows: Figure 2 .

[0034] Figure 2 (a) is the experimental result of compounding two foaming agents at different proportions. It can be seen that the foaming volume of the two surfactants is significantly increased after compounding, both exceeding 1000mL. The foaming volume of the compound system shows a trend of first decreasing, then increasing, and then decreasing again as the proportion of sodium α-olefin sulfonate increases. The results of the comprehensive foam value are shown in Figure 2. Figure 2 As shown in (b), when the ratio of laurylpropyl betaine:sodium α-olefin sulfonate = 2:4 (i.e., sodium α-olefin sulfonate: laurylpropyl betaine = 2:1), the foaming volume reaches 1123 ml, the separation time reaches 319 s, and the comprehensive foam value is the best.

[0035] Example 2

[0036] Al 3+ Gel foam, Ca 2+ Comparative experiment between gel foam and water-based foam.

[0037] Al 3+ Preparation method of gel foam: according to the total mass of high-stable gel foam that inhibits coal spontaneous combustion is 100g, the mass concentration of the foaming agent (sodium α-olefin sulfonate: lauramide propyl betaine = 2:1) is 0.3%, the mass concentration of the gelling agent (sodium alginate) is 0.5%, the mass concentration of the cross-linking agent (disodium ethylenediaminetetraacetic acid: polyaluminum chloride = 17:20) is 1.85%, the mass concentration of the pH modifier (gluconic acid-δ-lactone) is 1.5%, and the rest is deionized water.

[0038] First, the foaming agent is mixed with deionized water and stirred to obtain a mixed solution. Then, sodium alginate, a crosslinking agent, and glucono-δ-lactone are sequentially added to the mixed solution and foamed by mechanical foaming to form Al 3+ Gel foam.

[0039] Water-based foam: a composite foaming agent of sodium α-olefin sulfonate (AOS) and lauryl propyl betaine (LAB).

[0040] Ca 2+ Preparation method of gel foam:

[0041] (1) At room temperature, fatty alcohol polyoxyethylene ether sodium sulfate (AES) and polyether modified trisiloxane (GT-248) are compounded in a ratio of 2:3 to form a composite foaming agent (AG) with a mass fraction of 0.3%.

[0042] (2) EDTA-Ca crosslinker was prepared using disodium ethylenediaminetetraacetate (EDTA) and CaCl2 as raw materials in a molar ratio of 1:1. A certain amount of EDTA and CaCl2 were weighed and added to water. The mixture was stirred with a magnetic stirrer until it was completely dissolved to form an EDTA-Ca solution. Then, 5% NaOH was gradually added to the EDTA-Ca solution. The solution was titrated to a pH of about 7-8.

[0043] (3) 0.5 g of sodium alginate (SA) and 0.05 g of carboxymethyl cellulose (CMC) were dissolved in the AG solution to prepare the SA / CMC thickening solution. The solution was allowed to stand for 12 h to obtain the SC solution. Then, different amounts of EDTA-Ca and gluconolactone (GDL) were slowly added to the SC solution and thoroughly foamed using mechanical foaming (1500 r / min). The total solution volume was maintained at 100 g. Ca 2+ The preparation process of gel foam is as follows Figure 3 shown.

[0044] Water-based foam, Ca 2+ Gel foam, Al 3+ The gel foam was poured into beakers respectively and placed in a water bath for heating to conduct a temperature resistance test.

[0045] The following are water-based foams, Ca 2+ Gel foam, Al 3+ Comparison of three gel foams (invention).

[0046] Figure 4 (a) It can be seen that the water-based foam has no gel, so after the volume expands, the foam quickly breaks. Figure 4 (b) It can be seen that Ca 2+ The gel foam expanded the most, reaching 750ml, and its bubbles became significantly larger, but lasted longer, which shows that the introduction of gel greatly enhanced the strength of the foam. 2+ The gel foam drainage speed increased, the bubbles burst violently, and the volume decreased rapidly. Finally, at 285 minutes, the center point volume decreased to less than 250 ml. 3+ Gel foam, from Figure 4 (c) It can be seen that its volume is least affected by temperature. After its volume increases slightly, the middle of the foam first breaks and then collapses, and the total volume decreases. 2+ Unlike gel foam, most foams do not show obvious signs of growth, but shrink as the foam loses water. This is due to the interaction between sodium alginate and Al 3+ The chelation is relatively stable, the foam skeleton is strong, and the foam is not easy to break, so its volume is less affected by temperature. 3+Gel foam compared to Ca 2+ The ductility of gel foam decreases, and when the volume is large, it will break in the middle as the temperature rises.

[0047] Figure 5 (a) is the defoaming curve of three kinds of foams. It can be seen that the volume of foams at high temperature first expands and then shrinks. The temperature change at the center point of 250ml reflects the thermal insulation ability of the foam. Figure 5 (b) is the temperature resistance curve of three different foam systems. It can be seen from the figure that the ordinary water-based foam has the worst thermal insulation ability, and the foam volume has dropped below 250ml before the set temperature is reached. At this time, the temperature is 79.1℃. 2+ The thermal insulation capacity of gel foam is much higher than that of water-based foam, and its core temperature remains relatively stable after reaching 72.4°C. 3+ The maximum temperature at the center of the gel foam is stabilized at around 70.8°C, and its temperature resistance is significantly improved.

[0048] Example 3

[0049] The preparation methods of the three foams are the same as in Example 2.

[0050] 100g of each of the three foams were poured into a weighed empty beaker, and the total mass was measured and recorded after subtracting the empty beaker. The three foam systems were placed in a blast drying oven and dried at temperatures of 60°C, 80°C, 100°C, and 120°C, respectively. Each temperature was dried for 12 hours, and the samples were taken out of the blast drying oven and weighed every 1 hour to conduct a water retention test.

[0051] The following are water-based foams, Ca 2+ Gel foam, Al 3+ Comparison of three gel foams (invention).

[0052] from Figure 6It can be seen that the water-based foam has the highest water loss rate compared with the gel foam when dried at any temperature. At 100℃, it is completely dried in less than 7h. This is because the cross-linked structure of the gel foam makes the gel foam more stable and reduces the water loss rate. Therefore, the water evaporation of the two gel foams is relatively slow at the two temperature points of 60℃ and 80℃, and the water loss rate does not exceed 50% after drying for 12h. When the temperature is 100℃, the water loss rate of the gel foam increases significantly, which is because the water evaporation is more intense with the increase in temperature. When the temperature is 120℃, the water loss rate of the gel foam increases first and then decreases. This is because most of the free water in the gel foam has volatilized after 8h, and only some bound water remains in the gel structure, so the water loss rate slows down. In addition, the water loss rate of the gel foam is 97.54% after drying at 120℃ for 11h, and the water loss rate is 97.81% after 12h, and the mass hardly changes. This is because the remaining mass is the foam skeleton. Even if the water in the gel foam is completely evaporated, there is still a foam skeleton to isolate the coal from oxygen and inhibit the spontaneous combustion of coal. At the same time, it can be seen in the figure that Al 3+ Gel Foam with Ca 2+ Gel foam has higher stability than other foams.

[0053] Example 4

[0054] The preparation methods of the three foams are the same as in Example 2.

[0055] The original coal sample and the coal sample treated with gel foam were placed in a vacuum drying oven at 40°C for 24 hours and tested using a programmed temperature increase experiment. Figure 7 As shown, the raw coal sample, Ca 2+ Gel foam treatment of coal samples and Al 3+ Comparison of three coal samples treated with gel foam.

[0056] Figure 7 In (a), it can be observed that in the low-temperature oxidation stage before 115°C, the CO concentration of the three coal samples has a basically consistent trend, showing a slow increase. As the temperature continues to rise, the CO concentration of the raw coal sample increases rapidly and enters the accelerated oxidation stage. However, the temperature of the coal sample mixed with gel foam entering the accelerated oxidation stage is significantly delayed. Figure 7 (b) It can be seen that at the low temperature stage, the coal sample mixed with gel foam significantly inhibited the concentration of CO. This is because the evaporation of water contained in the gel foam lowered the temperature of the coal surface, and also played a role in wrapping and isolating oxygen, which controlled the generation of CO to a certain extent, indicating that the gel foam has the characteristic of inhibiting low-temperature oxidation. 3+ Gel foam is significantly better than Ca 2+ Gel foam, at different temperatures, increases by about 7%. 3+Gel foam compared to Ca 2+ Gel foam has a better dampening effect.

[0057] Example 5

[0058] The preparation methods of the three foams are the same as in Example 2.

[0059] The coal samples treated with gel foam and the raw coal samples were placed in a vacuum drying oven at 40°C for 24 hours and tested by thermogravimetric experiment. 2+ Gel foam treatment of coal samples and Al 3+ Comparison of three coal samples treated with gel foam Figure 8 As shown. Figure 8 It can be seen that the coal samples T1 and DTG1 treated with gel foam have been significantly improved compared with the original coal samples. This is because the structure of the gel foam is more stable and has better temperature resistance, thus delaying the maximum water loss temperature point. At the same time, the water retention performance is better, and the sample still retains more moisture after being placed.

[0060] from Figure 8 It can be seen that Al 3+ -GF has a T1 of 353K and a DTG1 of -1.65% / min. 2+ -GF's T1 (349.7K) increased by 3.3K, Ca 2+ -GF's DTG1 (-1.08% / min) increased by 0.57% / min, which was more obvious than that of the original coal sample. This is due to the fact that Al 3+ -GF has a more stable structure and better temperature resistance, thus delaying the maximum water loss temperature point. At the same time, it has better water retention performance and still retains more moisture after the sample is placed.

[0061] In Figure (a), the DTG of the raw coal sample is > 0 in the range of 450K to 550K, and the maximum value is close to 0.4% / min, and the mass increases significantly. As can be seen in Figure (b), Ca 2+ -GF treated coal samples also have a weight gain stage, but the increase is lower than that of the original coal samples. 3+ -GF's DTG is always below 0. This is due to Al 3+ -GF has a more stable structure, and after the water evaporates completely, it can leave a stronger film to wrap the coal body and prevent it from absorbing oxygen. 3+ The presence of can increase the apparent activation energy of coal reaction and reduce the activity of coal reaction. 3+ -GF shows better inhibition properties. 3 + -GF treated coal sample has a T2 of 742.1K, which is lower than that of Ca 2+- The 737.8K of coal sample T2 treated with GF was delayed by 4.3K, which was due to the Al 3+ -GF excellent water retention and coverage and Al 3+ Inhibitory effect on coal combustion.

[0062] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0063] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A highly stable gel foam for inhibiting spontaneous combustion of coal, characterized in that: The high-stability gel foam comprises the following components in terms of mass concentration: 0.3% of a foaming agent, 0.5% of a gelling agent, 1.85% of a cross-linking agent, 1.5% of a pH modifier, and the balance of deionized water.

2. The high-stability gel foam for inhibiting spontaneous combustion of coal according to claim 1, characterized in that: The foaming agent is a mixture of sodium α-olefin sulfonate and lauramide propyl betaine, and the mass concentration ratio of sodium α-olefin sulfonate to lauramide propyl betaine is 2:

1.

3. The high-stability gel foam for inhibiting spontaneous combustion of coal according to claim 1, characterized in that: The gelling agent is sodium alginate.

4. The high-stability gel foam for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The cross-linking agent is a mixture of disodium ethylenediaminetetraacetate and polyaluminium chloride, and the mass concentration ratio of disodium ethylenediaminetetraacetate to polyaluminium chloride is 17:

20.

5. The high-stability gel foam for inhibiting spontaneous combustion of coal according to claim 1, characterized in that: The pH modifier is glucono-delta-lactone.

6. A method for preparing a highly stable gel foam for inhibiting spontaneous combustion of coal, characterized in that: The high-stability gel foam comprises the following components in terms of mass concentration ratio: 0.3% of a foaming agent, 0.5% of a gelling agent, 1.85% of a cross-linking agent, 1.5% of a pH modifier, and the balance of deionized water. Firstly, the foaming agent and the deionized water are mixed in proportion, stirred evenly to obtain a mixed solution, and then the gelling agent, the cross-linking agent, and the pH modifier are sequentially added to the mixed solution, and after being completely mixed, a mechanical foaming method is used for foaming to form the gel foam.

Citation Information

Cited By

  • Microbial gel foam capable of suppressing explosion and inhibiting spontaneous combustion of coal and preparation method of microbial gel foam

    CN120591250A